KONSERVASI LAHAN DAN AIR DI HULU DAERAH ALIRAN SUNGAI (DAS) CITARUM MELALUI PENGEMBANGAN BUDIDAYA PERTANIAN SISTEM AGROFORESTRI - Mulyono, Daru (Jurnal Rekayasa Lingkungan)
The area of Citarum Watershed is cover six regencies: Bandung, Sumedang, Cianjur, Purwakarta, Bogor, and Karawang, West Java. The role and function of upper Citarum Watershed tend to declining, where total of deforestation area reach to a high of 560,095 ha or about 78 % from the total area and part of them already become critical area reach to a high of 143.798 ha. The Debit Ratio of Citarum River or Qmax/Qmin reach to a high of 1,667, it is indicate that Citarum Watershed become very critical condition and need appropriate management especially in the upper watershed. One altervative of the watershed management is application of agricultural forestry system where it is done by integrated development among agriculture, forestry, and animal husbandry. The successful application of agricultural forestry system will lead to conserve land and water where it will support flood control, agricultural irrigation, fisheries development, electric generation, industrial development, etc.Keywords: agricultural forestry, land conservation, watershed